Determinan Manajemen Laba melalui Struktur Kepemilikan, Pertumbuhan Penjualan dan Leverage - Tiara Octavia; Clara Susilawati (Journal of Management and Bussines (JOMB), 2023)
The aim of this research is to determine the influence of directors' compensation, managerial ownership, company size, company growth, and leverage on earnings management. The method used in this research is multiple regression analysis, the population in this study uses manufacturing companies listed on the IDX in 2019-2021. The research results show that directors' compensation, managerial ownership, company size, and company growth have a positive and significant effect on earnings management. Meanwhile, leverage has a positive and significant effect on earnings management. In conclusion, investors and creditors should be more careful in investing and lending the funds they have, because companies with low levels of leverage are indicated to be carrying out earnings management. Keywords: Earnings Management, Compensation, Ownership